Factor Analysis and Strategies for Regional Economic Development based on Creative Industry and Halal Lifestyle - Indra Fajar Alamsyah; Hantoro Ksaid Notolegowo; Md. Nazim Uddin (Al Tijarah, 2024)
The majority of regional economic development for cities is a top-down approach where the government designs programs and runs programs for the community. This has the consequence of policies that are not on target, thus an alternative path with a bottom-up approach is needed. As part of the United Nations Educational, Scientific and Cultural Organization (UNESCO) Creative Cities Network, Bandung City continues to nurture the economic growth of the creative sector. In fact, creative industry has been the backbone of the city's economy for many years. Bandung is also a multicultural city inhabited by many young Muslims, this city is a potential place for the movement of the halal economy. The halal lifestyle in the last few years has shown an increasing trend in among young people in Bandung. This study wants to explore the factors of regional economic development through the creative economy and halal lifestyle using the Exploratory Factor Analysis (EFA) method. This study involved 113 entrepreneurs related to the creative and halal industries. Based on the results of this study, there are four main factors that can increase regional economic development in Bandung through the creative industry and halal lifestyle: (Factor 1) Economic growth support system; (Factor 2) Intellectual support system; (Factor 3) Marketing support system; (Factor 4) Collaborative culture support system. These factors are alternative paths with a bottom-up approach as the foundation for regional economic development in Bandung. And based on the results of this study, there is a novelty in the form of a bottom-up approach for public policy related to regional economic development, especially urban regional economic development based on creative and halal industries.